To simplify 7C4 we use the combination formula given by:
nCr=n!/[(n-r)!r!]
thus:
In our case we shall have:
n=7 and r=4
7C4
=7!/[(7-4)!4!]
=5040/[6×24]
=5040/144
=35
The answer is 35
Answer:
.
Step-by-step explanation:
The given expression is
![\dfrac{3y^{\frac{1}{4}}}{4x^{-\frac{2}{3}}y^{\frac{3}{2}}\cdot 3y^{\frac{1}{2}}}](https://tex.z-dn.net/?f=%5Cdfrac%7B3y%5E%7B%5Cfrac%7B1%7D%7B4%7D%7D%7D%7B4x%5E%7B-%5Cfrac%7B2%7D%7B3%7D%7Dy%5E%7B%5Cfrac%7B3%7D%7B2%7D%7D%5Ccdot%203y%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%7D)
We need to simplify the expression such that answer should contain only positive exponents with no fractional exponents in the denominator.
Using properties of exponents, we get
![[\because a^ma^n=a^{m+n}]](https://tex.z-dn.net/?f=%5B%5Cbecause%20a%5Ema%5En%3Da%5E%7Bm%2Bn%7D%5D)
![\dfrac{1}{4}\cdot \dfrac{y^{\frac{1}{4}}}{x^{-\frac{2}{3}}y^{2}}](https://tex.z-dn.net/?f=%5Cdfrac%7B1%7D%7B4%7D%5Ccdot%20%5Cdfrac%7By%5E%7B%5Cfrac%7B1%7D%7B4%7D%7D%7D%7Bx%5E%7B-%5Cfrac%7B2%7D%7B3%7D%7Dy%5E%7B2%7D%7D)
![[\because a^{-n}=\dfrac{1}{a^n}]](https://tex.z-dn.net/?f=%5B%5Cbecause%20a%5E%7B-n%7D%3D%5Cdfrac%7B1%7D%7Ba%5En%7D%5D)
![\dfrac{x^{\frac{2}{3}}y^{\frac{1}{4}}}{4y^{2}}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%5E%7B%5Cfrac%7B2%7D%7B3%7D%7Dy%5E%7B%5Cfrac%7B1%7D%7B4%7D%7D%7D%7B4y%5E%7B2%7D%7D)
We can not simplify further because on further simplification we get negative exponents in numerator or fractional exponents in the denominator.
Therefore, the required expression is
.
Answer:
60% would be the correct answer
Step-by-step explanation:
Addition property of equality
Division property of equality
<em><u>Solution:</u></em>
<em><u>Given inequality is:</u></em>
3x - 2 > 4
![\mathrm{Add\:}2\mathrm{\:to\:both\:sides}](https://tex.z-dn.net/?f=%5Cmathrm%7BAdd%5C%3A%7D2%5Cmathrm%7B%5C%3Ato%5C%3Aboth%5C%3Asides%7D)
Here, Addition property of equality is used
When the same amount is added to both sides of an inequality, then the inequality is still true
3x - 2 + 2 > 4 + 2
3x > 6
![\mathrm{Divide\:both\:sides\:by\:}3](https://tex.z-dn.net/?f=%5Cmathrm%7BDivide%5C%3Aboth%5C%3Asides%5C%3Aby%5C%3A%7D3)
Here, Division property of equality is used
When we divide both sides of an equation by the same nonzero number, the sides remain equal.
![\frac{3x}{3}>\frac{6}{3}\\\\x > 2](https://tex.z-dn.net/?f=%5Cfrac%7B3x%7D%7B3%7D%3E%5Cfrac%7B6%7D%7B3%7D%5C%5C%5C%5Cx%20%3E%202)
Thus the property used in each step of solving the inequality is found
Answer:
y = -3x + 30
Step-by-step explanation:
First, find the slope using the slope formula:
m = (y2 - y1) / (x2 - x1)
m = (9 - (-3)) / (7 - 11)
m = -12/4
m = -3
Next, find the y-intercept by substituding one of the two points into what the equation is so far:
y = -3x + b
(7, 9)
9 = -3(7) + b
9 = -21 + b
30 = b
Now you have the full equation:
y = -3x + 30